Aplikasi Terapi Murottal Al-Quran Terhadap Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Nagrak Cianjur - Ega Apriliani; Burhanuddin Basri; Egi Mulyadi (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
Hypertension is an increase in systolic blood pressure of at least 140 mmHg or diastolic pressure of at least 90 mmHg. Hypertension is the main risk factor that can lead to heart disease, congestive heart failure, stroke, visual impairment and kidney disease. Murottal Al-Quran therapy is a therapy that can accelerate the reduction of blood pressure in patients with hypertension. Objective: To find out the effect of Al-Quran murottal therapy on blood pressure in patients with hypertension in the working area of ​​the Nagrak Cianjur Health Center. Results: After being given murottal Al-Quran therapy once a day for 7 consecutive days, the results of blood pressure decreased, namely from 160/100 mmHg to 155/100 mmHg, the second meeting from 150/100 mmHg to 140/90 mmHg, the third and fourth meetings from 140/100 mmHg to 130/90 mmHg, the fifth meeting from 140/90 mmHg to 130/90 mmHg and at the on the sixth and seventh day from 130/90 mmHg to 120/90 mmHg. Conclusion: The effect of murottal Al-Quran therapy on blood pressure in patients with hypertension.